Urban Drainage Management and Flood Control Improvement Using the Duflow Case Study: Aur Sub Catchment, Palembang, South Sumatra, Indonesia - Fraiture, Charlotte de; Susanto, Robiyanto Hendro; Suryadi, F.X.; Wahyu, Harrini Mutiara Hapsari (Makara Journal of Technology, 2017)
Urban flooding often times staggers the livelihood in an urban area, which most likely happens in the lowland urban area. Therefore, the existing urban drainage system should be improved in order to tackle the upcoming urban flooding events, which are more than likely to be more devastating than those in the previous years. The research location is in Palembang, Sumatra, Indonesia, where 30% of its urban part is a lowland area. The selected Aur Sub Catchment is located in Silaberanti. The main objective of this research is to improve the current drainage system in order to achieve the optimal design for urban drainage arrangement. This research was developed using Duflow Modelling Studio 3.8.3 in collaboration with ArcGIS 10.1 to schematize the drainage system and analyse the spatial and topographical condition of the research area. As a result, there are three development scenarios established by Duflow Modelling Studio in order to improve the drainage system in the research area. The first scenario is the current and extreme condition in the study area. The second scenario is the extreme condition, which is represented by the extreme rainfall. The third scenario is the improvement possibilities of the existing drainage system. There are three different types of improvements and modifications for the third scenario which are: canal dredging, canal dike/embankment, a pump installation, and a flap gate installation. In conclusion, based on three different scenario analyses, the most feasible, suitable, effective, and efficient alternative for overcoming the flooding in Silaberanti is a flap gate installation combined with dike construction in the flood risk sections of the river because it works automatically depending on the water level in the River.